2010
DOI: 10.1590/s0037-86822010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Análise da distribuição espaço-temporal de dengue e da infestação larvária no município de Tupã, Estado de São Paulo

Abstract: RESUMOMethods: Larval indices were built up block by block and for the entire municipality. We used the cross-lagged correlation method to assess the correlation between dengue cases and larval indices. The kernel estimator was used for spatial analysis. Results: The cross-lagged correlation between dengue cases and larval indices was significant. The kernel estimator maps of positive findings among recipients indicated heterogeneous distribution over the course of the study period. Over two years of transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
2
19
0
10
Order By: Relevance
“…Larval density and the number of dengue cases increased during the first four months of each year (period of high rainfall levels) and decreased between June and September (lower rainfall levels). These results were also found in studies conducted in São José do Rio Preto (SP) 23 , Maranhão (MA) 24 , Vila das Pedrinhas (SP) 25 and Tupã (SP) 32 .…”
Section: Rainfallsupporting
confidence: 74%
“…Larval density and the number of dengue cases increased during the first four months of each year (period of high rainfall levels) and decreased between June and September (lower rainfall levels). These results were also found in studies conducted in São José do Rio Preto (SP) 23 , Maranhão (MA) 24 , Vila das Pedrinhas (SP) 25 and Tupã (SP) 32 .…”
Section: Rainfallsupporting
confidence: 74%
“…If the biology of Ae. aegypti and the dengue virus, and the time taken until positive cases are registered in the information system is used to justify the period association with time lag 11,13,14 , then the results suggested that there was a higher positive correlation between BII and dengue fever when there was a two month time lag. This result agrees with Barbosa & Lourenço 14 , who concluded that the larval indicator shows the presence of adult mosquitoes in the municipality, although it is not the best indicator for measuring the risk of dengue occurrence.…”
Section: Continuementioning
confidence: 99%
“…No que tange a estudos sobre a dengue, Flauzino et al 37 verificou que os setores censitários mostram heterogeneidade espacial em relação às condições de vida, que, dentro de alguns setores, há diferenciais na distribuição espacial e temporal do risco de ocorrência da dengue e que a parcela economicamente ativa foi a mais atingida na área de estudo. A identificação dos locais que albergaram aglomerados de casos de dengue e sua caracterização demográfica e socioeconômica fornecem informações relevantes acerca do comportamento espacial dessa enfermidade, especialmente em ambientes urbanos diversos 38,39 . Estudo de revisão realizado por Flausino et al com propósito de avaliar o comportamento da doença identificou que, pelo fato de a dengue estar relacionada às características ecológicas do ambiente, os estudos devem utilizar não somente a geotecnologia (agregados de unidades espaciais), mas também associar esse recurso às características ambientais locais e a indicadores sociodemográficos para ampliar o entendimento da epidemia da dengue 37 .…”
Section: Aplicação Do Geoprocessamento Na Saúdeunclassified